Construction of a potato fraction library for the investigation of functional secondary metabolites. Issue 1 (2nd January 2019) - Nogawa, Toshihiko; Futamura, Yushi; Okano, Akiko; Suto, Mari; Nakamura, Junya; Ishihara, Katsuyuki; Osada, Hiroyuki
ABSTRACT: A potato fraction library was constructed to investigate functional secondary metabolites from 8 cultivars: Kitahime, Pilka, Sakurafubuki, Atlantic, Toyoshiro, Snowden, Kitamurasaki, and Northern Ruby, which were divided into flower, leaf, stem, roots, tuber peel, and tuber. Each fraction was a semi-purified extract and about 800 fractions were prepared for the library. They were analyzed by DAD-LC/MS to obtain structural information and were evaluated for various biological activities. LC/MS data showed that each part had a specific characteristic for their constituents supported by principal component analysis (PCA). Approximately 40% of fractions showed significant biological activities at 30 μg/mL, especially the flower fractions showed strong cytotoxicity. PCAs based on the activity and LC/MS data suggested that the strong cytotoxicity of flowers was derived from a complex mixture of potato glycoalkaloids. In addition, tuber peel fractions showed strong antimalarial activity, which had not been reported before. Also, some fractions showed significant antibacterial activities. Graphical abstract: : Potato fraction library was constructed to search for functional secondary metabolites. Flower and tuber-peel fractions showed potent cytotoxicity and antimalarial activity, respectively.